EVEKTIVITAS PROGRAM PENDIDIKAN POLITIK OLEH BADAN KESATUAN BANGSA DAN POLITIK KOTA BANDA ACEH DALAM MENINGKATKAN KESADARAN DEMOKRASI GENERASI MUDA - Puja lesati; Maulida Winda; Ayu Soraya; Nofriadi; Nadilati Fuddailah Fuddailah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Banda Aceh as a region with special autonomy has the authority to develop a democracy rooted in local values; however, the political awareness of youth remains relatively low. This study aims to analyze the implementation of political education programs by the National Unity and Politics Agency using the policy implementation theory of George C. Edward III. The research employs a descriptive qualitative method through interviews, observation, and documentation. The results show that the program has been implemented fairly well and has increased political participation, but it is not yet optimal. Communication remains one-way, resources are limited, and implementation is not sustainable, although the disposition of implementers and bureaucratic structure are adequate. Supporting factors include a strong legal basis and inter-institutional collaboration, while obstacles include low youth interest, program limitations, and the influence of social media. Overall, the program contributes to improving democratic awareness but requires innovation and more systematic evaluation to enhance its effectiveness and sustainability.